ISO 9000 implementation in public services : a comparative study of two public organizations in Ho Chi Minh City, Vietnam - Nguyen Diep Bich Hanh; Zimmerman, Willi; e; Donyaprueth Krairit; Project 300, Vietnam; AIT Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2007)
ISO 9000 is an international standard documentation system for quality management. This quality management system has been widely accepted and adapted as a national standard by many countries. However, the concept of applying quality standards to government functions is relatively new and has been applied in only a few countries among them Vietnam. Improving public administrative services delivery to people is one of the top priorities of the Public Administration Reform (PAR) in Vietnam. One-stop-shop (OSS) and ISO 9000 have been identified as instruments ensuring transparency, effectiveness and efficiency of the public administrative services delivery and of including citizens in the service improvements. OSS and sequential ISO implementation have been successful as confirmed by two case studies. Among the major factors are: A certain urgency of the reform in the recent past has been created; a vision for service improvements and a strategic planning have been developed by top politicians as well as high civil servants. The designation of public services suppliers of public organizations through OSS creates the foundation to set up and implement the quality management system ISO 9000. It has measurable components that - in case of deviation - allow for sanctioning. Thus, PAR, OSS and ISO have similar goals and complement each other very well. Specific factors for ISO 9000 implementation are: (i) Decisive leaders to implement ISO 9000 in public services; (ii) Preparation for personnel, working facility and clear empowerment; (iii) Hiring consultant organization; (iv) Assessment and comparing current status of the management of organization with the ISO 9000 quality system (with milestones) and among others (v) Training, writing and implementing and conducting internal audits before certification. In both case studies, certification and considerably high customer satisfaction have been achieved. Several difficulties remain such as constantly changing regulations, inadequate skills of staff and disparate locations of involved departments. Moreover, salary policies and incentives do not match with staffs efforts during ISO implementation process.
A research study submitted in partial fulfillment of the requirements for the degree of Master of Business Administration in International Public Management
Research Studies Project Report (M.B.A.) - Asian Institute of Technology, 2007
Keywords: ISO 9000 Series Standards; Quality assurance -- Vietnam; Public administration -- Vietnam